Partisipasi Masyarakat dan Permasalahannya pada Kampung Markisa di Kota Tangerang - Rahmat Budi Setiawan; Damanhuri Damanhuri; Ria Yuni Lestari (Journal of Civic Education, 2022)
The involvement of the community is needed in every development in the thematic villages. This study wants to show community participation in Kampung Markisa. The researcher uses descriptive qualitative method by using purposive sampling technique according to the criteria that have been made. Then for data analysis, researchers used data collection models, data reduction, data presentation, and conclusions. Meanwhile, the validity of the research data used source triangulation and technical triangulation. The results of this study shows that the participation of the people of Kampung Markisa are quite good that reflects from decision making, implementation, and evaluation. However, taking advantage of the benefits has not been maximized from the economic aspect, although from the environmental aspect there have been positive impacts. Regarding the responsibility in participating, the people of Kampung Markisa are disciplined in obeying regulations related to development, namely environmental change. Besides that the community is committed to the success of all development and maintaining the results of development in the future.